2020
DOI: 10.3390/ma13245710
|View full text |Cite
|
Sign up to set email alerts
|

Pultruded GFRP Reinforcing Bars Using Nanomodified Vinyl Ester

Abstract: Glass fiber-reinforced polymer (GFRP) reinforcing bars have relatively low shear strength, which limits their possible use in civil infrastructure applications with high shear demand, such as concrete reinforcing dowels. We suggest that the horizontal shear strength of GFRP bars can be significantly improved by nanomodification of the vinyl ester resin prior to pultrusion. The optimal content of functionalized multiwalled carbon nanotubes (MWCNTs) well dispersed into the vinyl ester resin was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Therefore, this may be a sign of interaction between epoxy matrix and nanofillers. 44,45,52 It can be interpreted that the decrease in peak density for nanofillers added samples reduces the autocatalytic effect due to agglomeration during curing proceses. 40,53 As seen in Figure 5, new band formation, which indicates the Si-O bending stretching groups was observed at 463 cm −1 in nano-silica and nano-hybrid added samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, this may be a sign of interaction between epoxy matrix and nanofillers. 44,45,52 It can be interpreted that the decrease in peak density for nanofillers added samples reduces the autocatalytic effect due to agglomeration during curing proceses. 40,53 As seen in Figure 5, new band formation, which indicates the Si-O bending stretching groups was observed at 463 cm −1 in nano-silica and nano-hybrid added samples.…”
Section: Resultsmentioning
confidence: 99%
“…Chennareddy et al 44 achieved a high increment in tensile strength by adding MWCNTs to GFR-laminated epoxy composites. Vemuganti et al 45 determined that MWCNTs addition into pultruded GFR/vinyl ester bars provided a 20% increase in tensile strength. Demirci et al 23 determined that nano-hybridization of nano-silica and MWCNTs showed an adverse effect compared to SiO 2 nanoparticle added Basalt Fiber-Reinforced (BFR) nanocomposites for the tensile and low-velocity impact responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the method relies on the pulling of continuous roving through a resin bath/impregnator, care must be taken during production using natural fibers due to their yarn’s low pull strength. As a result, pull speeds are usually limited to 100–200 mm/min, which is low when compared to the pull speeds used during glass fiber/epoxy processing [ 80 ].…”
Section: Processing Of Epoxy-based Natural Fiber Polymer Composite Ma...mentioning
confidence: 99%